PERENCANAAN PEMBANGUNAN BIDANG KETAHANAN PANGAN DI KABUPATEN PASURUAN - Luluk Khuroidah, Mrs. (FIA UB, 2012)
The research described and analyzed the areas of food security planning in Kabupaten Pasuruan. The research used a descriptive method and qualitative approach. Data sources were derived from informants and documents. The data collecting technique used interview and documentations. Data were analyzed using an interactive model. The results of this study were the field of food security development planning in Kabupaten Pasuruan shows that it is dominated by a top down approach. Planning mechanisms through forums musrenbang and technocratic had generally been in accordance with the planning cycle of Conyers and Hills. Kelompok Tani Nelayan Andalan (KTNA) was less involved in planning where many of their proposals were proposed through agricultural extension workers (PPL). so